PEMBUATAN ECOPRINT UNTUK MENINGKATKAN KETRAMPILAN MENGGUNAKAN BAHAN ALAM PADA PEMBELAJARAN SENI BUDAYA DAN PRAKARYA ANAK SEKOLAH DASAR DI KALIJAMBE SRAGEN: PEMBUATAN ECOPRINT UNTUK MENINGKATKAN KETRAMPILAN - Supriyadi, Slamet; Yulianto, Nanang; Margana; Widiyastuti, Endang; Yunianti, Esterica; Fauzi, Ali (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Making ecoprints to improve skills in using natural materials in learning arts and culture and crafts for elementary school children in Kalijambe, Sragen. Making this ecoprint means that the motifs produced on each fabric have different colors and patterns even though they use the same type of plant leaves. This is due to several factors, the relatively different shapes of the leaves. The introduction of ecoprinting to elementary school children creates a creative experience in learning arts and culture and crafts. Another contribution that can be achieved from this training is the growth of students' awareness of the potential of the environment and the desire to preserve nature. Ecoprint work training also provides real and meaningful learning experiences. Exploring the variety of natural materials around, especially leaves, adds value to aesthetic sensitivity. Apart from that, ecoprints also have quite a lot of selling value.